2021
DOI: 10.1002/wcms.1565
|View full text |Cite
|
Sign up to set email alerts
|

The role of metal ions in G protein‐coupled receptor signalling and drug discovery

Abstract: Metal ions, such as Na+, Mg2+, Ca2+, and Zn2+, are highly abundant in biological systems. For many G protein‐coupled receptors (GPCRs), metal ions, especially Na+, have been found to stabilize the receptors' inactivate state preventing receptor activation. Besides this role, recent studies indicated that metal ions can modulate ligand–GPCR interactions allosterically. These findings on ion‐mediated GPCR signaling open new vistas for understanding the functioning of GPCRs and further could help in designing pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 92 publications
1
16
0
Order By: Relevance
“…In our previous work, we reported the binding modes and orthosteric/allosteric effects of various metal ions (such as Na + , Mg 2+ , Ca 2+ , and Zn 2+ ) in GPCR signaling . Being one of the most abundant ions in the body, the sodium ion deserves more attention for its related mechanism in designing new GPCR ligands.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous work, we reported the binding modes and orthosteric/allosteric effects of various metal ions (such as Na + , Mg 2+ , Ca 2+ , and Zn 2+ ) in GPCR signaling . Being one of the most abundant ions in the body, the sodium ion deserves more attention for its related mechanism in designing new GPCR ligands.…”
Section: Discussionmentioning
confidence: 99%
“…Although the relationship between the fracture mechanisms and residual membrane stresses was established, the relationship between the multi-phases of Cu x Zn y and the multivalent metal ion pairs containing Cu 3+ /Cu 2+ /Cu + and Zn 3+ /Zn 2+ /Zn + was not. These multivalent ions are crucial for the human body’s biocatalytic reactions [ 46 ]. Furthermore, Cu bonded with polyester via nitrogen (N) to form a LROP structure, which was illustrated in our previous study of structural characterization, as shown at the right of Figure 2 [ 54 ].…”
Section: Other Stimuli and Chemotherapiesmentioning
confidence: 99%
“…The second problem is the low active pharmaceutical ingredients (API)-binding affinity, resulting in a lower API cargo carrier and a lesser choice of API variations. This could be solved by the hydrophobic grafting method through metallic surface chemical modification, or MOF [ 46 ]. The third problem is the toxicity of Cu, and this could be solved by using Zn ions in CuZn to control the toxicity [ 47 ].…”
Section: Introductionmentioning
confidence: 99%
“…Bond lengths were not given, but were reportedly consistent with a magnesium coordination complex [9].…”
Section: Introductionmentioning
confidence: 99%